The aortic arch baroreceptor response to static and dynamic stretches in an isolated aorta-depressor nerve preparation of cats in vitro. - Arndt, J O (1975)
1. The aortic arch baroreceptors of cats were studied in an isolated aortic arch-depressor nerve preparation in vitro to analyse their transmission properties. 2. Sinusoidal length changes of varying amplitudes (0-34-1-2 mm) and frequencies (1-10 Hz) at a given pre-stretch were imposed on the isolated receptor zone to quantitate the velocity sensitivity of these receptors and to test the linearity of the system. 3. The receptor response was evaluated from the spike activity of single fibres of the depressor nerve in number of spikes per stimulus period, average discharge rate, instantaneous frequency, and phase angle between forcing function and instantaneous frequency. 4. The static response is characterized by a threshold, saturation range, and a relatively large linear part between these two non-linearities. 5. The aortic receptors exhibit rate sensitivity. Depending on the stimulus amplitude and frequency the phase angles between the forcing function and the instantaneous frequency ranged from -14 to -68 degrees. 6. The average discharge rate (spikes/sec) is sensitive to stimulus amplitude but not to stimulus frequency at near-threshold operation; in the linear part of the static response curve, the receptor response becomes independent of the stimulus mode. 7. The baroreceptors of the aorta share many properties with other mechanoreceptors of different species and organ systems, particularly with those of the rest of the circulation. They exhibit static and to some degree rate sensitivity and operate physiologically near their thresholds, i.e. the afferent arc of the baroreflexes is highly non-linear.